HUBUNGAN PEMANFAATAN TUMBUHAN PASAK BUMI (Eurycoma longifolia Jack.) SEBAGAI OBAT TRADISIONAL DAN BIOAKTIVITASNYA - Silalahi, Marina (Jurnal Pendidikan Matematika dan IPA, 2019)
Pasak bumi (Eurycoma longifolia Jack.) is a species belonging Simarobuaceae has been long used as traditional medicine, which known very well as aphrosidiac. The studies have been conducted to reveal the benefits of E. longifolia through ethnobotany, phytochemical, and bioessay approaches, but the review articles on the its utilization and bioactivity limited. This article is based on scientific articles published on line or off-line, then synthesized so that to be information the relationship between use and bioactivity. Ethnobotany of E. longifolia have been used as a medicine for fever, malaria, improve stamina, antimalarial, antidiabetic, anticancer, aphrodisiac, overcoming erectile dysfunction. Bioactivity of E. longifolia is antiosteoporotic, antimicrobial, aphrodisiac, anticancer, angiogenesis, and hepatoprotective. Eurycomanone has activity as an antimalaria, antipyretic, aphrodisiac, and cytotoxic. The quassinoids, coumarin and glycosides of El have activity increase the production, quality, totality, synthesis and release of spermatozoa. Eurycoma longifolia is very potential to be developed as an antiosteoporotic and aprosidiac drug, but until now most of it is harvested directly from the forest, so to preserve it, we need to study the cultivation method.